Reviewing the Efficacy of Education on Professional Decision-Making Skills in Reducing Uncertainty to Select Clinical Specialty in Medical Students of Isfahan University of Medical Sciences, Iran - Masih Sabouri; Amir Behfar; Arash Hadadgar; Mohamadreza Abedi; Fatemeh Hadizadeh (مجله دانشکده پزشکی اصفهان, 2012)
Background: One of the reasons of uncertainty in choosing a specific clinical specialty is wrong decision-making. This study was conducted to train professional decision-making skills to medical students at internship and externship course levels in the form of a workshop. We also reviewed the impacts of the workshop on reducing indecisiveness in selecting a clinical specialty. Methods: This was a quasi-experimental study on 43 medical students at internship and externship course levels at Isfahan University of Medical Sciences, Isfahan, Iran. Before holding the workshop, students completed the hesitation and indecision scales. The participants were taught about decision-making skills for 15 hours. Immediately after the course and a month later, the students completed the same questionnaires again. The information and scores related to the pre-test, post-test, and one-month follow-up were analyzed using t-tests in SPSS. Findings: There was a significant difference in scores of hesitation scale at pre-test, post-test, and follow-up (P = 0.033). However, there was no significant difference in the scores of indecision scale (P = 0.151). There was no significant correlation between scores of students and different educational levels, sex, and marital status (P > 0.05). Therefore, training on professional decision-making skills reduced hesitation in selecting clinical specialty among medical students. However, it had no significant impact on their indecision. Conclusion: The professional decision-making skills training course reduced uncertainty in selecting clinical specialty among medical students. They were thus satisfied with participation in the course. They were also willing to attend complementary programs on selecting clinical specialty. Therefore, such an educational course is recommended to be held for all students who like to continue specialized studies in medicine during their medical course, especially in the first year of university.